ANALISIS HUBUNGAN PERSEPSI PERAWAT PELAKSANA TENTANG FUNGSI PENGAWASAN KEPALA RUANGAN DENGAN PELAKSANAAN STANDAR PROSEDUR OPERASIONAL TIMBANG TERIMA - Roifah, Ifa; Dwi Anggraini, Susanti (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Communication of various information provided by nurses in exchange shift (handover) was helpful for caring patient. The successful implementation handover patients was associated with controlled function. Research purpose was to analyze the relationship perception of nurses about the controlling function of head room with the handover standard operating procedures. Design research used correlational analytic with cross sectional approach. The population was all nurses who work in patient care room of Reksa Waluya Hospital which amounted to 41 peoples with a total sampling technique to obtain a sample that about the same with the number of population that are 41 peoples. Data retrieval used questionnaire and observation sheet and analyze by percentile and cross-tabulation. The results showed that from 23 respondents who have good perception are about 10 respondents they’re well behave, 3 respondents a bit unwell behave while doing handoverphase, and 10 respondents did not behave well. In conclusion there is no relationship perception of nurse head control room with execution standard operating procedure handover. Handover can work well if the supervision of the principal or the head of the room held a continuous basis, and based on standard operating procedures that have been agreed as a guideline in carrying out a job. Head room is expected to further improve supervision in accordance with standard procedures in order to improve the behavior of nurses in the implementation of standard procedures handover.Keywords: Perception, controlling, handover